2009
DOI: 10.1111/j.1464-410x.2008.08042.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of sexual function in patients receiving cryosurgery as a primary radical treatment for localized prostate cancer

Abstract: OBJECTIVE To evaluate prospectively the sexual function of patients undergoing cryosurgery as a primary radical treatment for localized prostate cancer, as the development of 17 G cryotherapy probes has improved the delivery of this treatment, but one of the side‐effects of cryosurgery is the development of erectile dysfunction (ED). PATIENTS AND METHODS Between July 2003 and May 2008, 53 patients were treated using an argon‐based third‐generation cryotherapy system (Oncura, Arlington Heights, IL, USA). Prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Impotence rates vary in the literature. Asterling et al published a prospective evaluation of sexual function in 53 patients who underwent cryosurgery as a primary treatment for prostate cancer with 39% of return of sexual function (28). Additionally, Lambert et al reported up to 71% return of potency in their study (29).…”
Section: Resultsmentioning
confidence: 99%
“…Impotence rates vary in the literature. Asterling et al published a prospective evaluation of sexual function in 53 patients who underwent cryosurgery as a primary treatment for prostate cancer with 39% of return of sexual function (28). Additionally, Lambert et al reported up to 71% return of potency in their study (29).…”
Section: Resultsmentioning
confidence: 99%
“…The most common complication was ED. The incidence of ED reported in the literature ranges from 49% to 94% at one year [3][4][5]21]. This complication occurs more frequently after cryotherapy than other local treatments, e.g., nerve-sparing radical prostatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The reported probability of maintaining EF were 60% for brachytherapy plus external-beam radiotherapy, 52% for external-beam radiotherapy, 25% for nerve-sparing prostatectomy and 15% for cryotherapy. 11 In terms of EF after cryoablation, there are only a few articles reporting longitudinal changes using either direct interview 12,13 or validated instruments. [14][15][16] Those reports describe that 39.0-51.3% of patients recover EF with penile rehabilitation or using erectile aids.…”
Section: Discussionmentioning
confidence: 99%